Common mode voltage reduction technique in a three‐to‐three phase indirect matrix converter. Issue 2 (2nd January 2018) - Rahman, Khaliqur; Al‐Emadi, Nasser; Iqbal, Atif; Rahman, Syed
Abstract : In this study, common mode voltage (CMV) reduction using space vector pulse‐width modulation (SVPWM) technique is proposed for a three‐phase induction motor drive fed by a three‐to‐three phase indirect matrix converter (MC). The proposed SVPWM effectively reduces the peak of the CMV without affecting the output voltage gain. By adopting the proposed SVPWM there is no change in the d v /d t of CMV at the terminal of the machine when compared to the existing method. The proposed control is possible by proper placement of zero vectors in the rectifier stage and discarding zero voltage vectors in the inverter stage of the indirect MC. The control technique is implemented in MATLAB/Simulink environment. Hardware setup is developed and control algorithm is implemented using dSPACE working in conjunction with the FPGA interface board. The results of the proposed SVPWM are compared with the existing method of CMV elimination and the improvement is established. The simulation results obtained are verified with the experimental results. The obtained results confirm a reduction of CMV by 48% (peak) and validate the viability of the proposed scheme in a three‐phase induction motor drive system.